2021
DOI: 10.1021/acscatal.0c04604
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Catalysis at the Liquid–Liquid Interface Microregion

Abstract: Liquid-liquid interfaces in principle have the potential to regulate the selectivity of chemical reactions because of large polar gradients and highly anisotropic microenvironments, but have not yet been well exploited. Here, we present an oil-water interface-based strategy to boost catalytic selectivity, exempli ed by selective hydrogenation of α,β-unsaturated aldehydes. The key to this success is the spatially controlled assembly of tubular catalyst particles at the narrow inner interfacial layer of Pickerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…It highlights the great potential for encapsulation of enzymes within the interior aqueous phase, paving the way for applications in interfacial biocatalysis. [39][40][41] The catalytic performance of lipase-loaded Pickering emulsion was initially examined by the esterification of 1-hexanol and hexanoic acid with toluene as the oil phase. In detail, lipase was dissolved and encapsulated in the internal aqueous droplet, while substrates and product were dissolved in the oil phase, with the catalytic reaction taking place at the w/o interface, as illustrated in Figure 4a.…”
Section: Resultsmentioning
confidence: 99%
“…It highlights the great potential for encapsulation of enzymes within the interior aqueous phase, paving the way for applications in interfacial biocatalysis. [39][40][41] The catalytic performance of lipase-loaded Pickering emulsion was initially examined by the esterification of 1-hexanol and hexanoic acid with toluene as the oil phase. In detail, lipase was dissolved and encapsulated in the internal aqueous droplet, while substrates and product were dissolved in the oil phase, with the catalytic reaction taking place at the w/o interface, as illustrated in Figure 4a.…”
Section: Resultsmentioning
confidence: 99%
“…L‐L and G‐L interfaces can exhibit other nanoscopic phenomena with potential impact for catalysis, such as interfacial acidification/basification, [175] local solvation, [176] surface charge, [177] presence of diffusion barriers, [178] and molecule [179] /catalyst [180] orientation. Also, the spatial assembly of catalytic particles at the inner/outer interfacial layer of emulsion droplets can condition the catalytic selectivity, as recently illustrated for cinnamaldehyde hydrogenation [181] . Overall, these studies are useful for designing theoretical descriptors allowing fast discovery of L‐L‐S and G‐L‐S systems for target reactions, including new and unprecedented reactions (e.g., electrochemical reactions) [182] …”
Section: Advanced Conceptsmentioning
confidence: 86%
“…[105] Typically, the past efforts to boost such a selectivity were restricted to the tunning of the structure and the electronic state of the catalyst. Recently, Yang et al [93] provided a new avenue towards the boosted selectivity of hydrogenation for the cinnamic aldehyde via a L/L interface-based strategy in Pickering emulsion. It was found that the method to make the reaction at the inner interfacial layer of a water droplet played a central role in the enhanced selectivity.…”
Section: Methodsmentioning
confidence: 99%
“…Reproduced from ref. [93] with permission from American Chemical Society, copyright 2021. found that the p-anisidine products were easily extracted to oil phase during the reduction reaction, facilitating the product separation. Likewise, our group reported the hydrodeoxygenation of water-soluble bio-oil (vanillin) at waterdecalin interface under Pickering emulsion stabilized by CNTs-supported Ru catalysts.…”
Section: Methodsmentioning
confidence: 99%